Exosomes in inflammation and cancer: from bench to bedside applications - Shiyuan Huang; Fang Yan; Yi Qiu; Tao Liu; Wenjin Zhang; Yige Yang; Rao Zhong; Yang Yang; Xi Peng (Molecular Biomedicine)
Abstract Exosomes, lipid bilayer nanovesicles secreted by nearly all cell types, play pivotal roles in intercellular communication by transferring proteins, nucleic acids, and lipids. This review comprehensively summarizes their multiple functions in inflammation and cancer. In inflammation, exosomes exhibit context-dependent pro- or anti-inflammatory effects: they promote acute responses by delivering cytokines and miRNAs to activate immune cells, yet suppress chronic inflammation via immunoregulatory molecules. Two representative inflammatory diseases, namely sepsis and inflammatory bowel disease, were highlighted to elucidate their roles in the acute and chronic inflammatory diseases. In cancer, exosomes orchestrate tumor microenvironment (TME) remodeling by facilitating angiogenesis, metastasis, and immune evasion through interactions with cancer-associated fibroblasts, tumor-associated macrophages, and extracellular matrix components. Furthermore, exosomes can facilitate the transition from inflammation to cancer by impacting pertinent signaling pathways via their transported oncogenic and inflammatory molecules. Tumor-derived exosomes also serve as non-invasive biomarkers correlating with disease progression. Clinically, exosomes demonstrate promise as therapeutic agents and drug carriers, evidenced by ongoing trials targeting inflammatory diseases and cancers. However, challenges in isolation standardization, scalable production, and understanding functional heterogeneity hinder clinical translation. Future research should prioritize elucidating cargo-specific mechanisms, optimizing engineering strategies, and advancing personalized exosome-based therapies. By bridging molecular insights with clinical applications, exosomes hold great potential in precision medicine for inflammation and oncology.